Edema induced with clomipramine - Baykara, Sema; Korkmaz, Sevda; Tasci, Gulay; Kaya, Suheda; Atmaca, Murad (Yerkure Tanitim & Yayincilik Hizmetleri A S, 2016)
Clomipramine is a tricyclic antidepressant acting by reuptake inhibition at both norepinephrine (NE) and serotonin (5HT) transporters. Blocking muscarinic receptors in peripheral tissues, it shows atropine-like effects and tolerance develops overtime against the anticholinergic effects. It may produce dizziness, drowsiness, headache, irritability, constipation, increased appetite, nausea, dry mouth, stomachache, changes in libido, increased sweating, and mild orthostatic hypotension. It may also depress cardiovascular reflexes related to the homeostasis of the system. The patient with diagnosis of major depressive disorder (MDB) developed mild facial puffiness with periorbital edema. The following days he developed local edema including the right hand and right forearm. In previous studies, it was reported that clomipramine exerts an anti-inflammatory effect by mast cell-dependent mechanism and by inhibition of neutrophil migration. Although clomipramine was suggested to develop edema in animal experiments, it has not been shown during the treatments in previous studies. The case would be a new report. Here, we present a case of a patient who developed local edema during use of clomipramine.
Keywords: clomipramine; edema; major depressive disorder